2011
DOI: 10.1182/blood-2010-08-299859
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hepcidin production during hypoxia-induced erythropoiesis in humans in vivo: data from the HIGHCARE project

Abstract: Iron is tightly connected to oxygen homeostasis and erythropoiesis. Our aim was to better understand how hypoxia regulates iron acquisition for erythropoiesis in humans, a topic relevant to common hypoxia-related disorders. Fortyseven healthy volunteers participated in the HIGHCARE project. Blood samples were collected at sea level and after acute and chronic exposure to high altitude (3400-5400 m above sea level). We investigated the modifications in hematocrit, serum iron indices, erythropoietin, markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
100
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 39 publications
19
100
1
3
Order By: Relevance
“…The effects of GSK1278863 on hemoglobin in both studies occurred with relatively small increases in plasma EPO concentrations, compared with changes in EPO concentration observed after administering injectable rhEPO. Measured plasma EPO concentrations in these studies remained within the range previously reported for patients with ESRD (range, 4.4-101.8 U/L) who were not treated with rhEPO 36 and were of similar magnitude to endogenous EPO concentrations seen during exposure to high altitudes, 37 whereas rhEPO concentrations were at least 12-fold higher in the rhEPO control group in the HDD study than in any of the GSK1278863 groups across both studies. Thus, GSK1278863 can increase (nondialysis patients not taking rhEPO) or maintain (HDD patients switched from rhEPO) hemoglobin while maintaining physiologic EPO concentrations.…”
Section: Discussionsupporting
confidence: 51%
“…The effects of GSK1278863 on hemoglobin in both studies occurred with relatively small increases in plasma EPO concentrations, compared with changes in EPO concentration observed after administering injectable rhEPO. Measured plasma EPO concentrations in these studies remained within the range previously reported for patients with ESRD (range, 4.4-101.8 U/L) who were not treated with rhEPO 36 and were of similar magnitude to endogenous EPO concentrations seen during exposure to high altitudes, 37 whereas rhEPO concentrations were at least 12-fold higher in the rhEPO control group in the HDD study than in any of the GSK1278863 groups across both studies. Thus, GSK1278863 can increase (nondialysis patients not taking rhEPO) or maintain (HDD patients switched from rhEPO) hemoglobin while maintaining physiologic EPO concentrations.…”
Section: Discussionsupporting
confidence: 51%
“…In vivo, hypoxia has been shown to decrease hepcidin expression in both acute and chronic experimental models 21,38,39 as well as in humans. 40 Hypoxia is also known to induce the expression of renal erythropoietin, thereby promoting increased erythropoiesis to compensate for the decrease in ambient oxygen. The delayed hepcidin decrease in response to hypoxia in vivo could, therefore, be explained by the time needed to mount an increase in erythropoietic activity.…”
mentioning
confidence: 99%
“…An important component is a reduction in hepcidin levels analogous to that seen during hypoxia at high altitude. 11 Roxadustat (also known as FG-4592) is an oral HIF-PH inhibitor (HIF-PHI). By inhibiting HIF-PHs and mimicking the response to a cellular reduction in oxygen levels, roxadustat increases HIF activity and promotes erythropoiesis.…”
mentioning
confidence: 99%